Monitoring and Analysis of Compensatory Trunk Movements with RGB-D Camera and Wireless System for Rehabilitation of Upper Limbs - Garcia, Alice; Kelbouscas, André; V. e Silva, Sibyla; Guimarães, Leonardo; de Oliveira, Vinícius (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2020: Anais do XII Simpósio Brasileiro de Robótica e XVII Simpósio Latino Americano de Robótica, 2020)
Assistive Robotics has been shown to be an important tool in the patient rehabilitation process. The rehabilitation of patients with traditional therapeutic approaches has not achieved results, making therapeutic approaches that use robotics gain more and more strength. With this, a series of new ones can be used in order to assist in the rehabilitation of patients with limited restrictions, especially those who have suffered post-stroke trauma. Stroke patients often use the trunk to compensate for impaired upper limb motor function during upper limb rehabilitation training, or that results in a reduced effect of rehabilitation training. Detecting trunk displacements can improve the effect of rehabilitation training. Therefore, this study aims to use an RGB-D camera to analyze the movement behavior of the trunk of five volunteers, who do not have in the execution of four predefined any type of restriction, movements. The objective is to verify that, even without any type of restriction, the process of executing movements of the trunk to execute movements. In addition, this study proposes a methodology to perform kinematic tracking of trunk movement compensation through the use of a wireless system. The results obtained with the use of the RGB-D camera were satisfactory and were able to prove the existence of compensatory movements even in patients who do not have any type of restriction.